The Application of Fixed Asset Revaluation Method for the FOOD Distributor Company PT XYZ and the Benefit in TAX - Justianto, Alexius; Murtaqi, Isrochmani (Journal of Business and Management, 2013)
Tax can be defined as the expense which must be paid by people or companies to the country and it is applied by the government to build our country. There are many ways in applying tax planning in order to minimize the amount of tax by â€œlegal wayâ€. One of that legal ways to minimize the tax burden is by applying revaluation method. This research is about the application of fixed asset revaluation method and the relatedness with income tax expense which must be paid. nevertheless if the result from this research shows that this revaluation method is benefit to be applied, PT XYZ will be recommended to execute this fixed asset revaluation for the vehicle. The writer presupposes that this research is executed in the end of 2011. For the next 8 years (from 2011 to 2019), it will be researched more whether it is more benefit to use fixed asset revaluation method or continue the previous system (historical method). Fixed asset revaluation can act as double-edged sword. One side it can decrease the income tax expense, but in one side the company must pay income tax caused by the increasing of asset value. The result of this research shows that by using PT XYZâ€™s discount rate of 4,67%, the revaluation method is worth to be applied in PT, and it shows the positive NPV Rp 37.731.211,-. From interpolation method, it is known that IRR of applying revaluation method in PT. XYZ is percentage of discount rate 12,74%., where in percentage of discount rate 12,74%, the revaluation method will not give benefit anymore (NPV = 0). The revaluation method will not worth to be applied (negative NPV) if the discount rate is more than 12,74%. Fortunately, the discount rate of PT. XYZ is less than 12,74% (4,67%), so the revaluation method is worth to be applied (positive NPV).Â Keywords: tax planning, the revaluation method for fixed assets----------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.